Pengaruh financial attitude, income, locus of control, financial literacy terhadap financial management behavior gamers yang melakukan transaksi lootbox pada game Genshin Impact - Adiputra, Prima William; Harlina Meidiaswati (Universitas Negeri Surabaya, 2025)
This study aims to investigate the factors that can influence the financial management behaviour of Genshin Impact gamers who engage in lootbox transactions. The study employs a quantitative approach; this research utilises primary data collected from 176 individuals characterised as gamers who have an income and have made transactions within Genshin Impact. The collected data was processed using SEM-PLS (Structural Equation Modelling-Partial Least Squares) analysis with the aid of SmartPLS 4 software. The results of this study indicate that the variables financial attitude and locus of control have a significant effect on financial management behaviour. In contrast, the variables income and financial literacy do not influence financial management behaviour. Therefore, the impliactions of this research highligt the importance for gamers to cultivate positive financial attitudes through awareness in managing expenses, savings and long-term goals. Gamers who actively engage in in-game transactions should strengthen internal control to resist external pressures such as lootbox promotions or community influence, enabling more rational decisions aligned with personal needs and financial capacity. Moreover, gamers need to understand that the higher the income does not automatically lead to good financial management behavior; effective financial management is required regardless of income level. Financial literacy should be applied into daily habits so that it can supports more sustainable financial decisions, rather than just theoretical understanding. Consistent financial management behavior can help gamers avoid impulsice spending and maintain financial well-being